Zits. Undivided inattention - Scott, Jerry, 1955- (Andrews McMeel Publishing, 2021)
The latest relatable, hilarious, and outstanding Zits treasury includes the complete comics from 2020. A year's worth of Zits cartoons, all in one place! This fantastic Zits treasury includes the timeless teenage antics of Jeremy, whose fridge-clearing appetite, garage band dreams, and legendary laziness constantly baffle and amuse his parents, friends, and girlfriend. Featuring the award-winning combination of Jerry Scott's trademark humor and Jim Borgman's brilliant line art, Zits is the perfect comic for anyone parenting a teenager, or who remembers the glorious time in life when you're old enough to enjoy the privileges of adulthood, but too young to be crushed by its responsibilities.